2018
DOI: 10.1080/19420862.2018.1545510
|View full text |Cite
|
Sign up to set email alerts
|

Engineered pH-dependent recycling antibodies enhance elimination of Staphylococcal enterotoxin B superantigen in mice

Abstract: A new modality in antibody engineering has emerged in which the antigen affinity is designed to be pH dependent (PHD). In particular, combining high affinity binding at neutral pH with low affinity binding at acidic pH leads to a novel antibody that can more effectively neutralize the target antigen while avoiding antibody-mediated antigen accumulation. Here, we studied how the in vivo pharmacokinetics of the superantigen, Staphylococcal enterotoxin B (SEB), is affected by an engineered antibody with pH-depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Previous efforts to engineer pH-sensitive protein–protein interactions guided this work. The naturally pH-dependent interaction between human IgG1 Fc and the neonatal Fc receptor (FcRn) has been engineered to adjust antibody in vivo half-lives ( 26 , 27 , 28 ), while novel pH-dependent binding has been introduced into other binding partners via histidine scanning mutagenesis ( 15 , 29 ). In both cases, pH sensitivity relies on the presence of ionizable histidines in the binding interface, whose pK a of ∼6.0 can be modulated by adjacent residues.…”
Section: Resultsmentioning
confidence: 99%
“…Previous efforts to engineer pH-sensitive protein–protein interactions guided this work. The naturally pH-dependent interaction between human IgG1 Fc and the neonatal Fc receptor (FcRn) has been engineered to adjust antibody in vivo half-lives ( 26 , 27 , 28 ), while novel pH-dependent binding has been introduced into other binding partners via histidine scanning mutagenesis ( 15 , 29 ). In both cases, pH sensitivity relies on the presence of ionizable histidines in the binding interface, whose pK a of ∼6.0 can be modulated by adjacent residues.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, it is interesting to note that despite the increased affinity for FcRn at neutral pH, these sweeping variants have no effect on endogenous IgG levels contrarily to the ABDEG developed by Argenx discussed later in Section 3 , which has a much stronger affinity for FcRn at neutral pH [ 71 ]. The sweeping antibody technology has shown promising results in neutralizing the staphylococcal enterotoxin B in a murine model, decreasing the toxin levels, and opening a new way for treating some bacterial infections [ 73 ]. Finally, a recent proof of concept has been published by Bogen et al who have generated a bispecific sweeping antibody targeting two tumor antigens, one CEACAM5, in a pH-dependent manner, and the other CEACAM6 in a pH-independent manner.…”
Section: Antibody Modifications That Enhance Igg Half-life and Biodis...mentioning
confidence: 99%
“…A recent study showed the application of recycling and sweeping antibodies for the removal of toxins. The activity of conventional and pH-responsive variants of an antibody against Staphylococcal enterotoxin B (SEB) superantigen in a mouse model were compared [ 32 ]. Although all analyzed antibodies neutralized the toxin and reduced cytokine production, the pH-responsive molecules eliminated the toxin significantly faster than the conventional molecules.…”
Section: Targeting Soluble Antigens With Antibodies Releasing Antigenmentioning
confidence: 99%
“…In the case of eculizumab, a small library of 66 variants was created by replacing each position within CDRs by histidine [ 27 ]. In other examples, 20 variants of anti-SEB antibody 3E2 were designed as yeast displayed scFvs, but only nine of them were successfully expressed, suggesting that introduced histidine affected folding [ 32 ]. Some properties of mutants can be predicted with reasonable accuracy by computational methods.…”
Section: Generation Of Ph-responsive Antibodiesmentioning
confidence: 99%
See 1 more Smart Citation